Assessment of quality of care of patients with ST-segment elevation myocardial infarction. Issue 8 (1st December 2020) - Hudzik, Bartosz; Budaj, Andrzej; Gierlotka, Marek; Witkowski, Adam; Wojakowski, Wojciech; Zdrojewski, Tomasz; Gil, Robert; Legutko, Jacek; Bartuś, Stanisław; Buszman, Paweł; Dudek, Dariusz; Gąsior, Mariusz
Abstract : Aims: The 2017 European Society of Cardiology guidelines for the management of ST-elevation myocardial infarction recommended assessing quality of care to establish measurable quality indicators in order to ensure that every ST-elevation myocardial infarction patient receives the best possible care. We investigated the quality indicators of healthcare services in Poland provided to ST-elevation myocardial infarction patients. Methods and results: The Polish Registry of Acute Coronary Syndromes is a nationwide, multicentre, prospective study of acute coronary syndrome patients in Poland. For the purpose of assessing quality indicators, we included 8279 patients from the Polish Registry of Acute Coronary Syndromes hospitalised with ST-elevation myocardial infarction in 2018. Four hundred and eight of 8279 patients (4.9%) arrived at percutaneous coronary intervention centre by self-transport, 4791 (57.9%) arrived at percutaneous coronary intervention centre by direct emergency medical system transport, and 2900 (37.2%) were transferred from non-percutaneous coronary intervention facilities. Whilst 95.1% of ST-elevation myocardial infarction patients arriving in the first 12 h received reperfusion therapy, the rates of timely reperfusion were much lower (ranging from 39.4% to 55.0% for various ST-elevation myocardial infarction pathways). The median left ventricular ejection fraction was 46% and was assessed before discharge in 86.0% of patients. Four hundred and eighty-nine of 8279 patients (5.9%) died during hospital stay. Optimal medical therapy is prescribed in 50–85% of patients depending on various clinical settings. Only one in two ST-elevation myocardial infarction patients is enrolled in a cardiac rehabilitation program at discharge. No patient-reported outcomes were recorded in the Polish Registry of Acute Coronary Syndromes. Conclusions: The results of this study identified areas of healthcare system that require solid improvement. These include direct transport to percutaneous coronary intervention centre, timely reperfusion, guidelines-based medical therapy (in particular in patients with heart failure), referral to cardiac rehabilitation/secondary prevention programs. Also, there is a need for recording quality indicators associated with patient-reported outcomes.